Review of Milton A. Cohen, Hemingway’s laboratory: the Paris in our time - Monk, Craig (My University, 2006)
The slim chapbook published in Paris as in our time (1924) by William Bird’s Three Mountains Press represents for Milton Cohen an essential precursor to all of Ernest Hemingway’s subsequent works. While the volume’s eighteen vignettes, written over a period of seven months, gave the fledgling Hemingway something to contribute to a series of texts assembled and promoted by Ezra Pound, critical appreciations of that work have treated in our time as little more than undistinguished juvenilia. With extant volumes fetching as much as six figures at auction, the 170 copies of the work printed are of most interest today to rare book collectors, exceeding in renown even first editions of James Joyce’s Ulysses (1922) as desirable artifacts of Paris in the 1920s. Cohen hopes to move beyond a simple acknowledgment of the formal innovations in this unusual little text to argue that all elements of the mature Hemingway’s writings are, in fact, discernable in embryonic form on the pages of in our time. Indeed, the central trope of Hemingway’s Laboratory obliges readers to accept that the novelist sought to distance himself from his earliest writings through a great deal of willful experimentation. In examining Hemingway’s extensive trial and error through this period, however, Cohen also discovers a number of elements of his writing, consistent with a burgeoning modernism, that never found their way into his mature prose.
Keywords: Hemingway\; Ernest; chapbooks